ChemInform Abstract: Synthesis of Enamides by Ruthenium‐Catalyzed Reaction of Alkyl Azides with Acid Anhydrides in Ionic Liquid. Issue 17 (April 2016) - Pak, Han Kyu; Han, Junghoon; Jeon, Mina; Kim, Yongjin; Kwon, Yearang; Park, Jin Yong; Rhee, Young Ho; Park, Jaiwook
Abstract: 50 examples